Income Distribution and Inequality in Indonesia: Study on Middle Class Household - Maipita, Indra; Wahyudi, Setyo Tri (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2017)
The current positive trend of Indonesiaâs economic growth has demonstrated that increasing income per capita is one of the economic prosperity indicators. One pillar of the increase in the income per capita of middle class is its surge to 56.5% in 2010 compared to that of in 2000 which only reached 20%, and it has brought Indonesia to be qualified as a middle-income country. It is believed that, one of the ways to reduce inequality in society is by encouraging economic growth and development of middle-class society. This study aims to analyze the profile of middle class household and its contribution on decreasing inequality in Indonesia using the data of National Survey of Social Economy (Susenas) from 2004 to 2012. By using Keynesian Consumption model and Lorenz Curve, the results showed that middle-class grouping by using the 20th and 80th percentile of income has a higher growth than that of the USD or portion average income approach. However, due to the relatively small contribution of middle class income growth in Indonesia to the economic growth, the changes on Indonesian middle class income is inelastic to the changes on national output.